Criteria and indicators of experimental study of the aesthetic education of high school students (Pedagogy of Higher and Secondary Education, 2012)
Batrak T. V. Criteria and indicators of experimental study of the aesthetic education of high school students.The criteria and indicators for the experimental study of aesthetic breeding of high school pupils in secondary school are defined in the article. The author also describes the levels of aesthetic breeding, based on the correlation of criteria.
Keywords: aesthetic breeding; the criteria of esthetical education; indicators; the levels of aesthetic breeding.